EVpedia: an integrated database of high‐throughput data for systemic analyses of extracellular vesicles. Issue 1 (20th March 2013) - Kim, Dae‐Kyum; Kang, Byeongsoo; Kim, Oh Youn; Choi, Dong‐sic; Lee, Jaewook; Kim, Sae Rom; Go, Gyeongyun; Yoon, Yae Jin; Kim, Ji Hyun; Jang, Su Chul; Park, Kyong‐Su; Choi, Eun‐Jeong; et al.
Abstract : Secretion of extracellular vesicles is a general cellular activity that spans the range from simple unicellular organisms (e.g. archaea; Gram‐positive and Gram‐negative bacteria) to complex multicellular ones, suggesting that this extracellular vesicle‐mediated communication is evolutionarily conserved. Extracellular vesicles are spherical bilayered proteolipids with a mean diameter of 20–1, 000 nm, which are known to contain various bioactive molecules including proteins, lipids, and nucleic acids. Here, we present EVpedia, which is an integrated database of high‐throughput datasets from prokaryotic and eukaryotic extracellular vesicles. EVpedia provides high‐throughput datasets of vesicular components (proteins, mRNAs, miRNAs, and lipids) present on prokaryotic, non‐mammalian eukaryotic, and mammalian extracellular vesicles. In addition, EVpedia also provides an array of tools, such as the search and browse of vesicular components, Gene Ontology enrichment analysis, network analysis of vesicular proteins and mRNAs, and a comparison of vesicular datasets by ortholog identification. Moreover, publications on extracellular vesicle studies are listed in the database. This free web‐based database of EVpedia (http://evpedia.info ) might serve as a fundamental repository to stimulate the advancement of extracellular vesicle studies and to elucidate the novel functions of these complex extracellular organelles.